Dental Radiation Safety In Radiography Policies: Scoping Review And Findings In Indonesia - Illiyana, Himma; Basabih, Masyitoh (Pusat Publikasi Nusantara, 2023)
Radiation safety is important to prevent deterministic and stochastic effects on patients. The aims of this review are to summarize and provide an overview of radiography policies on dental radiation safety and to identify the gaps between Indonesia’s radiography policies with worldwide best practices. The review is based on the PRISMA-ScR. Articles are searched through Embase, Pubmed and Scopus. Articles focused on dental radiation safety are included with addition of policy documents found by manual searching. Results are summarized in a table and in-text and analyzed by comparing with policies in Indonesia.Ten articles are collected and identified as policy statement (n = 2), guideline (n = 2), and recommendation (n = 6). Three themes are used to summarize the findings: (1) target, (2) qualified expert, and (3) best practice. The result shows that all policies have incorporated safety radiation principles. Radiography policies regulates: dental practitioners and trained operators as personnel qualified to conduct radiography examination; appropriate technique and practical measures; x-ray maintenance and radiological testing. The scope of radiography policies in Indonesia is extensive, with health facilities and service providers as the primary policy targets